Spinal HMGB1 participates in the early stages of paclitaxel-induced neuropathic pain via microglial TLR4 and RAGE activation - Moraes, Thamyris Reis; Veras, Flavio Protasio; Barchuk, Angel Roberto; Nogueira, Ester Siqueira Caixeta; Kanashiro, Alexandre; Galdino, Giovane (Frontiers in Immunology, 2024)
Introduction: Chemotherapy-induced neuropathic pain (CINP) is one of the main adverse effects of chemotherapy treatment. At the spinal level, CINP modulation involves glial cells that upregulate Toll-like receptor 4 (TLR4) and signaling pathways, which can be activated by pro-inflammatory mediators as the high mobility group box-1 (HMGB1).Objective: To evaluate the spinal role of HMGB1 in the paclitaxel-induced neuropathic pain via receptor for advanced glycation end products (RAGE) and TLR4 activation expressed in glial cells.Methods: Male C57BL/6 Wild type and TLR4 deficient mice were used in the paclitaxelinduced neuropathic pain model. The nociceptive threshold was measured using the von Frey filament test. In addition, recombinant HMGB1 was intrathecally (i.t.) injected to confirm its nociceptive potential. To evaluate the spinal participation of RAGE, TLR4, NF-kB, microglia, astrocytes, and MAPK p38 in HMGB1-mediated nociceptive effect during neuropathic pain and recombinant HMGB1-induced nociception, the drugs FPS-ZM1, LPS-RS, PDTC, minocycline, fluorocitrate, and SML0543 were respectively administrated by i.t. rout. Microglia, astrocytes, glial cells, RAGE, and TLR4 protein expression were analyzed by Western blot. ELISA immunoassay was also used to assess HMGB1, IL-1β, and TNF-α spinal levels.The pharmacological experiments demonstrated that spinal RAGE, TLR4, microglia, astrocytes, as well as MAPK p38 and NF-kB signaling are involved with HMGB1-induced nociception and paclitaxel-induced neuropathic pain. Furthermore, HMGB1 spinal levels were increased during the early stages of neuropathic pain and associated with RAGE, TLR4 and microglial activation. RAGE and TLR4 blockade decreased spinal levels of pro-inflammatory cytokines during neuropathic pain.Taken together, our findings indicate that HMGB1 may be released during the early stages of paclitaxel-induced neuropathic pain. This molecule activates RAGE and TLR4 receptors in spinal microglia, upregulating pro-inflammatory cytokines that may contribute to neuropathic pain.